Effect of MWCNTs added by electrostatic flocking method on adhesion of carbon fiber prepreg/Nomex honeycomb sandwich composites. (5th August 2017) - Chen, Chao; Li, Yanxia; Gu, Yizhuo; Li, Min; Zhang, Zuoguang
Abstract: To improve the adhesion of face sheet and core in sandwich composites, multi-walled carbon nanotubes (MWCNTs) were added by the electrostatic flocking method to reinforce the adhesive fillet. MWCNTs on surface and sub-surface of face sheet were taken into account to analyze the effect of adding locations of MWCNTs. The sandwich composites with different weight contents of MWCNTs were prepared by autoclave process. The size of adhesive fillet confirmed that the electrostatic flocking method could ensure the forming quality of sandwich composites with self-adhesive prepreg skin. Climbing drum peel test and flexural test were adopted for mechanical assessment. The results showed that the process of MWCNTs on sub-surface demonstrated a remarkable enhancement of both the peel properties and flexural properties for samples with 1.5 wt% MWCNTs in comparison to the samples of pure prepreg. The reinforcing mechanism was analyzed by the microstructures of adhesive fillet and it is found that the different enhancement effect was attributed to the distribution features of MWCNTs in the adhesive fillet. Graphical abstract: Highlights: The electrostatic flocking method was employed to attach MWCNTs to face sheet prepregs in honeycomb sandwich composites. MWCNTs on surface and on sub-surface of face sheet were adopted to analyze the effect of adding locations. This method solved the problem of high resin viscosity raised by MWCNTs for self-adhesive prepreg. The process of MWCNTs on sub-surface demonstrated a remarkable enhancement of peel properties with 1.5 wt% MWCNTs. The reinforcing mechanism and the different enhancement effect were analyzed by the microstructures of adhesive fillet.